2021
DOI: 10.3390/agronomy11061146
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Profiles and Antioxidant Activity of Cultivated and Wild Tomato Seedlings under Low-Temperature Stress

Abstract: Low temperature is a major limiting factor for the growth and reproduction of some plant species, such as tomato. So far, few studies have been conducted on the effects of low temperature, and the mechanisms of plants’ response to this type of stress is not fully clear. In the current study, the effects of low, nonfreezing temperature (10 °C for three days) on the hormone content, antioxidant activity, and expression patterns of cold-related genes in the leaves of cold-tolerant species (Solanum habrochaites Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…This was also found for other abiotic stresses, such as metal toxicity (C.L. Li et al, 2021; Yuan et al, 2013; Yuan & Huang, 2016; Zhao et al, 2017), drought (Chu et al, 2010), salt stress (Chen et al, 2012; Korver et al, 2018) and cold damage (Heidari et al, 2021; Shibasaki et al, 2009). For example, the Mn‐ and Cd‐stress‐induced reduction of IAA content in root apices leads to inhibited root growth (Yuan & Huang, 2016; Zhao et al, 2017), whereas Cu and Al toxicity increases auxin concentrations, which likewise inhibits root growth (C.L.…”
Section: Discussionmentioning
confidence: 65%
“…This was also found for other abiotic stresses, such as metal toxicity (C.L. Li et al, 2021; Yuan et al, 2013; Yuan & Huang, 2016; Zhao et al, 2017), drought (Chu et al, 2010), salt stress (Chen et al, 2012; Korver et al, 2018) and cold damage (Heidari et al, 2021; Shibasaki et al, 2009). For example, the Mn‐ and Cd‐stress‐induced reduction of IAA content in root apices leads to inhibited root growth (Yuan & Huang, 2016; Zhao et al, 2017), whereas Cu and Al toxicity increases auxin concentrations, which likewise inhibits root growth (C.L.…”
Section: Discussionmentioning
confidence: 65%
“…Hormones content, antioxidant activities, and downstream signals are induced in response to environmental stresses to control cell stability and mitigate the negative effects of ROS ( Abdullah et al, 2021 ; Heidari et al, 2021 ). These results indicated that the key regulatory components of the biosynthetic pathways in ABA and ethylene changed significantly during the T. hispida response to Cd stress.…”
Section: Resultsmentioning
confidence: 99%
“…When plants are subjected to cold or heat (both ends of the temperature spectrum), the endogenous bioactive GA levels are much lower than at optimal temperatures (Figure 1C) [34,37,[44][45][46][47]. This leads to a shorter stem/hypocotyl of pea/soybean seedlings or reduced plant height of ryegrass at moderately low temperature or heat [34,[44][45][46] and plant growth cessation at chilling temperatures [37,48,49].…”
Section: Temperature Dose-modulated Monophasic Responsesmentioning
confidence: 99%
“…Different to the apparent monophasic patterns of jasmonates and gibberellins, the levels of auxin and brassinosteroids (BR) do not strictly follow the monophasic pattern across the temperature range [51][52][53]. Moderately low temperature causes a reduction of endogenous auxin levels and plant growth limitation [47,54], e.g. a shorter hypocotyl or primary root in soybean [44] and Arabidopsis [55], respectively.…”
Section: Temperature Dose-modulated Monophasic Responsesmentioning
confidence: 99%